Chile (Journal of Parents and Teachers, 2026)
On the map, Chile stands out as the longest, narrowest and highest country. It is also one of the countries with the most islands in the world. It is the leading producer of copper and fertilisers. Ferdinand Magellan, a Portuguese in the service of Charles V, arrived from the south. After five months, they discovered a narrow passage to the west, which was named the Strait of Magellan. When they reached the open sea, they found calm waters, so Magellan named it the Pacific Ocean. Colonisation arrived twenty years later with Pedro de Valdivia, while the liberator and father of the Chilean nation was Bernardo O'Higgins, a Creole of Irish descent.
Keywords: Chile; Strait of Magellan; copper and nitrate; the Andes